Teaching content reading and writing - Ruddell, Martha Rapp (J. Wiley, 1997)
Literacy in middle and secondary schools; Literacy processes: thinking, reading and writing; Comprehension instruction in content areas; Vocabulary learning in content areas; Reading across the curriculum; Writing across the curriculum...